Enhancement of voip and video streaming performance over IEEE802.11e WLAN - Hameed, Shihab A.; Hour, Bahi J. A. (IIUM Press, 2011)
There are various versions of IEEE802.11 WLAN in the market, and each applies different modulation technique and operates in different frequency bands. For example, the IEEE 802.11 b version provides data rates up to 11 Mb/s on the wireless medium, applying complementary code keying (CCK) and direct sequence spread spectrum (DSSS) as modulation technique. It operates in the industrial, scientific, and medical (ISM) band at 2.4 GHz. On the other hand, the IEEE 802.11 a version operates in the unlicensed 5 GHz band, and provides data rates up to 54 Mb/s on the wireless medium, applying the multicarrier technique orthogonal frequency-divi sion multiplexing (OFDM) as the modulation technique [1]. The 802.11 g version applies the same multicarrier modulation technique as 802.11 a, but operates in the 2.4 GHz ISM band like 802.11 b. However, due to channel conditions and protocol overhead, the maximum achievable throughput on the MAC layer is less than the data rate available on the wireless medium for the mentioned IEEE 802.11 versions